Characterization of fluoropolymer films deposited by magnetron sputtering of poly(tetrafluoroethylene) and plasma polymerization of heptadecafluoro-1-decene (HDFD) on (100)-oriented single-crystal silicon substrates - Zhang, Y. (2014)
10.1002/sia.1243